An Assessment of Climate Engineering from a Buddhist Perspective. (24th February 2018) - Markus, Till; Vivekānanda, Bhikkhu; Lawrence, Mark
Abstract : This article expounds a Buddhist perspective on the rapidly emerging topic of Climate Engineering, i.e. the deliberate, large-scale manipulation of the environment as a proposed means to counteract anthropogenic climate change or some of its specific aspects like global mean temperature increase. It sets the stage with two orthogonal aspects: an overview of the topic of Climate Engineering, and a broader analysis of the Buddhist perspective on mankind's relationship with nature. Linking these together, we show that as one of the world's major faiths, Buddhism can provide valuable insights and perspectives for the evolving global discourse on Climate Engineering methods, and that it advocates some basic requirements concerning their further development and possible future deployment.